Passive signal processing techniques for miniature fibre fabry-perot interferometric sensors - Ezbiri, A (Cranfield University, 1996)
This thesis describes new signal processing techniques applicable to miniature low finesse Fabry-Perot interferometric sensors. The principle of operation behind the techniques presented resides in the use of the axial modes from a single multimode laser diode to produce a series of phrase shifted interferometric outputs in conjunction with the path imbalance of the sensor microactivity.